2023
DOI: 10.1021/acs.est.3c05321
|View full text |Cite
|
Sign up to set email alerts
|

A Coculture of Photoautotrophs and Hydrolytic Heterotrophs Enables Efficient Upcycling of Starch from Wastewater toward Biomass-Derived Products: Synergistic Interactions Impacting Metabolism of the Consortium

Minmin Pan,
Yiru Wang,
Jens O. Krömer
et al.

Abstract: Even with particular interest in sustainable development, due to the limited types of bioavailable carbon sources that could support heterotrophic/mixotrophic growth, microalgae-derived products still suffer from inconsistent yield and high costs. This study demonstrates a successful cocultivation of the photoautotroph Chlorella vulgaris with a hydrolytic-enzyme-abundant heterotroph, Saccharomycopsis fibuligera , enabling efficient starch upcycling from water/wastewater toward enhancing microalgae-dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Previous studies indicated that the central carbon metabolism (including glycolysis, TCA cycles, and pentose phosphate pathway) was the main carbon metabolic pathway of the Streptomyces genus. , In a cocultured strains (Chlorella vulgaris and Saccharomycopsis fibuligera) consortium, the expressions of most genes encoding the conversion from glucose to pyruvate of Chlorella vulgaris (glycolysis pathway) were significantly up-regulated, indicating a highly stimulated consumption of glucose by the Chlorella vulgaris . The stronger carbon source metabolism performance (especially carbohydrate) of the strains coculture in this study indicated that the glycolysis pathway was significantly enhanced.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…Previous studies indicated that the central carbon metabolism (including glycolysis, TCA cycles, and pentose phosphate pathway) was the main carbon metabolic pathway of the Streptomyces genus. , In a cocultured strains (Chlorella vulgaris and Saccharomycopsis fibuligera) consortium, the expressions of most genes encoding the conversion from glucose to pyruvate of Chlorella vulgaris (glycolysis pathway) were significantly up-regulated, indicating a highly stimulated consumption of glucose by the Chlorella vulgaris . The stronger carbon source metabolism performance (especially carbohydrate) of the strains coculture in this study indicated that the glycolysis pathway was significantly enhanced.…”
Section: Resultsmentioning
confidence: 47%
“…Moreover, the potential quorum sensing and syntrophic pathway between the two strains drove specific pollutant removal. Therefore, the cross-feeding, quorum sensing, and syntrophic pathway might be the cooperation mechanism for two strains of actinomycetes coculture. , …”
Section: Resultsmentioning
confidence: 99%